Reading social relations from Roman African mosaics – an iconographic analyse - Mech, Anna (Studia Europaea Gnesnensia, 2017)
The paper presents the diversity of Roman African society and the relations between different social groups by analysing the representations on the mosaics. It also analyses the manner of self-presentation of the landowners and their wives.